2006
DOI: 10.2217/14796678.2.4.467
|View full text |Cite
|
Sign up to set email alerts
|

Cytoskeletal Basis of Ion Channel Function in Cardiac Muscle

Abstract: SummaryThe heart is a force-generating organ that responds to self-generated electrical stimuli from specialized cardiomyocytes. This function is modulated by sympathetic and parasympathetic activity.In order to contract and accommodate the repetitive morphological changes induced by the cardiac cycle, cardiomyocytes depend on their highly evolved and specialized cytoskeletal apparatus. Defects in components of the cytoskeleton, in the long term, affect the ability of the cell to compensate at both functional … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 73 publications
1
10
0
Order By: Relevance
“…Indeed, it has been reported that the biomechanical stress during myocardium contraction-relaxation cycles may contribute to determining an altered ion channel localization, thus possibly influencing the ionic properties of cardiac tissue. 17,18 An SNP in the KCNE1 gene (A to G at position 112), leading to a glycine substitution for serine at amino acid position 38, has been identified. 19 The functional significance of the S38G polymorphism in the KCNE1 gene remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, it has been reported that the biomechanical stress during myocardium contraction-relaxation cycles may contribute to determining an altered ion channel localization, thus possibly influencing the ionic properties of cardiac tissue. 17,18 An SNP in the KCNE1 gene (A to G at position 112), leading to a glycine substitution for serine at amino acid position 38, has been identified. 19 The functional significance of the S38G polymorphism in the KCNE1 gene remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Mutations in scaffolding and/or cytoskeletal “channel interaction proteins” (ChIPs) are recognized causes of LQT syndrome (Ackerman and Mohler 2010). Mutations in caveolin-3 (Vatta et al 2006), alpha-1 syntrophin (Ueda et al 2008; Wu et al 2008a), and β IV spectrin (Hund et al 2010; Wu et al 2008a; Sarhan et al 2009; Vatta and Faulkner 2006) are associated with increased magnitude of late I Na and with LQT and/or SIDS. Proteins such as F-actin, telethonin, α-actinin-2, and Z-band alternatively spliced PDZ-motif (ZASP) that are anchored at the Z-line may participate in the trafficking of ion channels to the T-tubule membrane (Vatta and Faulkner 2006).…”
Section: Congenital Causes Of Late Inamentioning
confidence: 99%
“…Mutations in caveolin-3 (Vatta et al 2006), alpha-1 syntrophin (Ueda et al 2008; Wu et al 2008a), and β IV spectrin (Hund et al 2010; Wu et al 2008a; Sarhan et al 2009; Vatta and Faulkner 2006) are associated with increased magnitude of late I Na and with LQT and/or SIDS. Proteins such as F-actin, telethonin, α-actinin-2, and Z-band alternatively spliced PDZ-motif (ZASP) that are anchored at the Z-line may participate in the trafficking of ion channels to the T-tubule membrane (Vatta and Faulkner 2006). A mutation in telethonin is reported to increase Na + window current (Mazzone et al 2008), and a missense mutation in ZASP shifts the voltage dependence of Na + channel activation (Li et al 2010).…”
Section: Congenital Causes Of Late Inamentioning
confidence: 99%
“…2 Site-directed mutagenesis of the S196L mutation in the ZM4 motif was performed as previously described. …”
Section: Co-immunoprecipitation (Co-ip)mentioning
confidence: 99%
“…Replacement of deranged myocardium by fibrous tissues has been proposed as a likely mechanism of reentrant tachycardia and/or conduction disease, but very little is known about the cellular mechanisms connecting cytoskeletal alterations to arrhythmias in DCM. 2 …”
mentioning
confidence: 99%